PENGARUH LINGKUNGAN KERJA, DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PADA PR. TRUBUS ALAMI (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to examine and analyze the Effect of Work Environment, Work Discipline and Work Motivation on the Performance of Production Section Employees in Public Relations. Trubus Alami Kab. Malang both partially and simultaneously. In this study the population amounted to 85 employees and all were taken as samples. Data collection through questionnaires, data analysis in this study using SPSS version 22. The sampling technique uses quantitative methods, while the data testing techniques used in this study include validity test, reliability test, classic assumption test, multiple linear regression analysis, and testing the research hypothesis. The results of the analysis show that partially or simultaneously the work environment, work discipline and work motivation have a positive and significant effect on employee performance on public relations. Trubus Alami Kab. Malang.Keywords: Work Environment, Work Discipline, Work Motivation and Employee Performance.